SISI GENDER DALAM PEMIKIRAN ISLAM LIBERAL NURCHOLISH MADJID - Lukman Hakim; Mohammad Nasir Omar (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2010)
Issues around gender equality framed in feminism movement is one of discourses that attracts attention of muslim scholars recently. The gender mainstreaming is backgrounded by the reality that women are viewed as a second class. It is likely due to the domain of religious interpretation tends to side with patriarchal. As a response, some scholars try recall the balance thoughts in order that women may be placed to their nature position. Nurchalis Madjid one of those who took part in the discourse and gave very substantial thought on the issue. He opines that Islam is a religion that emphasize justice and equality among mankind, which equalitybetween sexes is included in. There is only god-fearing gauges one’s glory at side of Allah. It is owing to the fact that god-fearing is an achievement that can be possibly reached by all mankind without any exception. glory obtained is based on one’s achievement.